Effectiveness of Video-Assisted Project Based Learning (PjBL) Model in Improving Student Learning Outcomes - Yusal, Yulianti; Laili, Ummiy Fauziah; Sa’id, Ibrahim Bin; Nurlaili, Eva Alvi; Sari, Meirita (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
The purpose of this study was to determine whether there is a significant difference between the learning outcomes of students taught using the video-based Project Based Learning model and students taught using conventional learning. This research used quasi-experimental method with Posttest Only Control Design research design. The research was conducted at MTs Al-Manar using two classes as samples, the two classes were class IX C as the experimental class and class IX D as the control class. The instruments used in this study are learning outcomes test questions, learning outcomes questionnaires and learning implementation observation sheets. Data analysis used descriptive statistical analysis and inferential statistical analysis. The results of descriptive statistical analysis showed that the average score in the control class was 75.65, while the average in the experimental class was 82.21. Inferential statistical analysis was carried out by means of t-test (independent sample T-Test test). Based on the results of the Independent Sample T-Test test, the sig (2-tailed) value is 0.001, meaning that sig <0.05 so that H0 is rejected and H1 is accepted. From the results of these calculations, the researcher concluded that there was a significant difference between the learning outcomes of ninth grade students of MTs Al-Manar who were taught using a video-based Project Based Learning model and students who were taught using conventional learning.